Brands of violence: crime and the ugly in Brazilian abolitionist poetry - Simpson, Pablo [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2017)
This presentation aims to investigate some images of horror in Brazilian abolitionist poetry. There is in Castro Alves, in poems like Lucia or Tragedia no lar, the representation of slavery suffering from the dimension of ugliness: in the blood dew, in the unburied corpse, in the bed of agonies. It is also in Fagundes Varela, in the filthy rags, in the uncured wounds of the poem The slave. This investigation will seek these images from the eventual transit of Christian representations, as in Castro Alves's The Mother of the Captive: O Mother! Do not awaken the sleeping soul, / With the sublime verb of the Martyr of the Cross!
Keywords: Abolitionism; Aesthetic; Brazilian romantic poetry; Crime; Ugly